Threaded rods grouted in beech laminated veneer lumber. Issue 4 (25th March 2022) - Wirries, Jonas; Tsopjio, Franck Y. T.; Vallée, Till; Myslicki, Sebastian
Abstract: Glued‐in rods are a class of adhesively bonded joints for timber engineering applications resulting in high‐strength and stiffness connections. However, the use of polymeric adhesives may lead to issues related if the temperatures exceed their glass transition temperature, restricting their performance under quasi‐static, or more critically, sustained loads. To overcome these, the substitution of polymeric adhesives by mineral high‐performance grout was investigated. It was found that primers have neither a significant effect on strength nor on the failure mode; threated wood surfaces, however, resulted in a significant improvement of the latter. Based thereupon, grouted‐in rods were manufactured. The best performance was achieved with a threaded wood surface, which achieved roughly 50% of the strength comparable adhesively bonded glued‐in rod's strength. While the obtained strength may seem quite low, it is important to remind that the latter will largely remain unaffected by temperature; accordingly, made at room temperature, the comparison between grouted and glued rods is in favor of adhesive bonding, it may well be different at elevated ones.